Better Bank Management for Sustainability - Empirical Risk Evidence from Vietnam - TUAN, PHAM VAN; HUY, DINH TRAN NGOC; ANH, VU THI KIM; HUNG, LE MANH (The journal of contemporary issues in business and government, 2021)
Vietnam has reached a low inflation rate of 06% in year 2015, so it is good to see what happen in bank management during the post- low (L) inflation time 2015-2020, in order to propose plans to maintain banking business management sustainability. Within volatility of multi macro factors, this paper will estimate bank risks with Beta CAPM measurement in the nation in the above selected period. Next step, we aims to measure and evaluate how much macro factors effects in the market risk of 7 big listed banks with semiannual data. We use synthesis statistics methods, and dialectical materialism method, combined with econometric model with 9 macro variables, and figure out that lending rate and risk free rate have inverse effects on market risk. It implies that increase in lending rate will cause market risk declines whereas increase in Rf will cause beta increases. Then, we will suggest recommendations for improving bank management capabilities for sustainable bank management and governance. We recognize that modern advanced bank management solutions are needed for incoming periods. JEL classification numbers: M21, G12, G30, E58, E62